Mining of single nucleotide polymorphism (SNP) and simple sequence repeats (SSRs) from EST tropical fruits (Asian Journal of Plant Biology, 2014)
The advancement in genomics technology has produced vast amount of expressed sequencetags (ESTs) sequence from tropical fruits. These resources have increased the publicavailability of ESTs sequence from year after year. Therefore, this effort permits mining ofsingle nucleotide polymorphism (SNP) and simple sequence repeat (SSR) from EST tropicalfruits. SNP and SSR are types of molecular marker which commonly used in modern geneticanalysis for wide application such as diversity analysis, linkage analysis and association study.In this study, a small scale EST sequences from tropical fruits (pineapple, mango, coconut andbanana) were retrieved from dbEST database (www.ncbi.nlm.nih.gov/dbEST/ ) as of March2013. Various bioinformatics tools were applied for rapid discovery of SNP and SSR markerfrom EST sequences. We analyzed 31,920 unigenes (contigs and singletons) representing atotal of 77,418 ESTs from four tropical fruits for their potential use in developing SNP and SSRmarkers. A total of 13,709 EST-SNP were discovered while a total of 4853 EST-SSR werediscovered from these four tropical fruits. The most abundant EST-SSR repeat is fromtrinucleotide (15,957 repeats) followed by dinucleotide (13,797 repeats) and tetranucleotide(973 repeats). Here, 1738 primers from SNP while 2033 primers from SSR were passedthrough the setting criteria and were selected for validation using genotyping platform. Thisstudy not only serves as a resource for marker development in tropical fruits but can provide abetter insight into the selection of candidate genes of interest.